IMPACT OF SERVICE QUALITY ON SATISFACTION AND LOYALTY OF TOURISTS IN RURAL TOURISM OF ŠUMADIJA AND WESTERN SERBIA - Perić, Goran; Dramićanin, Sandra; Gašić, Marko (Economics of Agriculture, 2020)
The issue of rural tourism service quality does not retain a sufficiently important place in the existing domestic and foreign literature. The purpose of this research in service quality, which is an important initiator of tourist satisfaction and loyalty in rural tourism. The survey was conducted at the beginning of 2020 using a questionnaire based survey method to 299 respondents. With the purpose of checking the impact of the service quality on the satisfaction and loyalty of tourists in rural tourism of Šumadija and Western Serbia, an analysis was performed using SEM - Structural Equation Modeling. The survey results point there is a direct correlation between service quality and satisfaction, and as well between loyalty and satisfaction. Between service quality and loyalty there is not a direct link, but there is a large indirect effect by satisfaction. The implications of this research, limitations and future research recommendations for are outlined.